Early Childhood Stress and Child Age Predict Longitudinal Increases in Obesogenic Eating Among Low-Income Children - Miller, Alison L. (Acad Pediatr, 2018)
OBJECTIVE: To identify whether psychosocial stress exposure during early childhood predicts subsequent increased eating in the absence of hunger (EAH), emotional overeating, food responsiveness, and enjoyment of food. METHODS: This was an observational longitudinal study. Among 207 low-income children (54.6% non-Hispanic white, 46.9% females) early childhood stress exposure was measured by parent report and a stress exposure index was calculated (higher scores indicating more stress exposure). Eating behaviors were measured in early (M: 4.3 (SD 0.5) years) and middle (M: 7.9 (SD 0.7) years) childhood. Observed EAH was assessed by measuring kilocalories of palatable food the child consumed after a meal. Parents reported on child eating behaviors on the Child Eating Behavior Questionnaire. Child weight and height were measured and body mass index z-score (BMIz) calculated. Multivariable linear regression, adjusting for child sex, race/ethnicity, and BMIz, was used to examine the association of stress exposure with rate of change per year in each child eating behavior. RESULTS: Early childhood stress exposure predicted yearly increases in EAH (β=0.14, 95% confidence interval (CI) 0.002, 0.27) and Emotional Overeating (β=0.14, 95% CI 0.008, 0.27). Stress exposure was not associated with Food Responsiveness (trend for decreased Enjoyment of Food; β=−0.13, 95% CI 0.002, −0.26). All child obesogenic eating behaviors increased with age (p’s<.05). CONCLUSIONS: Early stress exposure predicted increases in child eating behaviors known to associate with overweight/obesity. Psychosocial stress may confer overweight/obesity risk through eating behavior pathways. Targeting eating behaviors may be an important prevention strategy for children exposed to stress.